Administration Under Occupation: Evaluations of a Dilemma - Romijn, Peter (Hispania Nova, 2021)
This text explores the relevance of the study of the Administration for the analysis of occupation regimes during Second World War. In order to do this, the article focuses on the case study of Dutch local authorities, which played an important role both in the realities of occupation and adaptation and in the apparently contradictory dynamics of oppression and collaboration. This contribution also addresses the parameters through which transitional justice was exercised and the recovery of Dutch society after the Nazi occupation was addressed.
Keywords: occupation; the Netherlands; local administration; accomodation; collaboration